Effect of alkali pretreatment on removal of lignin from sugarcane bagasse - Wunna, Kyaw (Animo Repository, 2017)
Lignin is complex polymer compound contained in woody plant tissue. In sugar extraction and bioethanol production from lignocellulosic materials, it is necessary to remove lignin due to its recalcitrant nature. The present work aimed to study the effect of alkali pretreatment on removal of lignin from sugarcane bagasse using sodium hydroxide. Two solid loading conditions (20 %w/v and 10 %w/v) were used in this study. For 20 % loading condition, base concentrations were varied at four levels and autoclaving time was varied at 3 levels, and the experiments were performed in 12 runs for this loading rate. For 20 % w/v solid loading, the concentrations of sodium hydroxide were 0.5 wt%, 1.0 wt%, 1.5 wt%, and 2.0 wt% at 121 °C for 10 min, 30 min and 60 min. For 10 % loading condition, the levels of each factor were increased. The base concentrations were varied at six levels and autoclaving time was varied at 5 levels, and the experiments were also performed, resulting in 30 runs for this loading rate. For 10 % w/v solid loading, concentrations were 0.5, 1.0 wt%, 1.5 wt%, 2.0 wt%, 3.0 wt% and 4.0 wt% at 121 °C for 10 min, 30 min, 60 min, 90 min and 120 min. The maximum removal of lignin for 10 % solid loading was 83.7 % under the conditions of 2.0 wt% sodium hydroxide at 121 °C for 60 min. For 10 % solid loading, 87.3 % of lignin removal was achieved in 1.5 wt% sodium hydroxide at 121 °C for 30 min. The result showed that increased solid loading may cause insufficient removal of lignin during alkaline pretreatment. Copyright © 2017, AIDIC Servizi S.r.l..